Effect of Sources of Self-Efficacy in Mathematics on Self-Assessment in Mathematics - González Franco, Verónica (Consorcio de Universidades Mexicanas A.C., 2022)
Self-efficacy in mathematics generated by various sources of information is essential for the development of the real ability of students in the area of mathematics. The aim was to analyze the effect of the sources of self-efficacy in mathematics on the beliefs of self-efficacy evaluated via self-assessment in university students from northwestern Mexico. Three hundred ninety-one (391) psychology and engineering university students answered the Scale of Sources of Self-efficacy in Mathematics, which allows the evaluation of four sources of self-efficacy (master's experience, vicarious experience, social persuasion and physiological states) as well as a self-assessment in math performance. The results of the confirmatory factor analysis by modeling structural equations identified a significant and direct relationship of the sources of information of self-efficacy in mathematics on the self-assessment of students regarding their ability in mathematical activities, as well as the usefulness of the scale in the population studied.